2022
DOI: 10.3390/molecules27030623
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Metabolomic Analysis of Amaranthus cruentus Grains Harvested at Different Stages

Abstract: This study aimed at investigating the impact of early versus normal grain harvesting on the chemical composition and secondary metabolites of Amaranthus cruentus species grown in South Africa. Mature harvested grain had higher (p < 0.05) DM, CF, NDF and ADF content compared to prematurely harvested grain. There were no significant (p > 0.05) differences between CP, ADL and GE of premature and mature harvested grains. Mature harvesting resulted in higher grain Ca, P, Mg and K content. Essential amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…З цього погляду насіння амаранту є сировиною, що забезпечує високу харчову цінність [1]. Родина Amaranthacea включає 70 видів [2]. Види Amaranthus hypochondriacus L., A. cruentus L. і A. caudatus L. вирощуються для отримання насіння [3].…”
Section: вступunclassified
See 1 more Smart Citation
“…З цього погляду насіння амаранту є сировиною, що забезпечує високу харчову цінність [1]. Родина Amaranthacea включає 70 видів [2]. Види Amaranthus hypochondriacus L., A. cruentus L. і A. caudatus L. вирощуються для отримання насіння [3].…”
Section: вступunclassified
“…UDC 577.112+664.34:633.2:631.526.3 Liubych, V. V. 1* , Kononenko, L. M. 1 , Poltoretska, N. M. 1 , & Voitovska, V. I. 2 Purpose. To determine the peculiarities of the formation of the nitrogen component and the fatty acid composition in amaranth seeds of different varieties.…”
mentioning
confidence: 99%
“…Amaranth is a C 4 plant of great agronomic importance because of its high nutritional and nutraceutical values which provide health benefits. Manyelo et al [ 40 ] reported higher calcium (Ca), P, magnesium (Mg) and potassium (K) contents (2771.07, 5024.56, 3501.36 and 5101.99 mg/kg, respectively) in the grain and significantly higher trace mineral content for Copper (Cu), manganese (Mn), zinc (Zn) and iron (Fe) (5.95, 23.71, 49.97 and 147.01 mg/kg, respectively). In addition, secondary metabolites, specifically anthocyanins, were shown to be abundant in grains (35.92 mg/kg), which reinforces its potential in increasing the immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Amaranth grains contain phenolic compounds (e.g., flavonoids) and a relatively high antioxidant capacity, where total phenolic acids in several amaranth ecotypes range from 16.8 to 40.1 mg/100 g (dry weight) [8]. Nevertheless, the phytochemical composition depends on multiple variables during growing conditions [9].…”
Section: Introductionmentioning
confidence: 99%